2022
DOI: 10.3390/curroncol29110685
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Pembrolizumab Dosing Interval in Advanced NSCLC with PD-L1 TPS ≥ 50%: 3 Weekly Compared to 6 Weekly Dosing

Abstract: Background: A fixed dose of 200 mg of pembrolizumab every 3 weeks (Q3W) is the standard of care for patients with stage IV non-small cell lung cancer (NSCLC) and PDL1 ≥50%. In April 2020, based on pharmacokinetic modeling without formal comparative studies, the FDA approved 400 mg every 6 weeks (Q6W). Pharmacokinetic studies also suggested comparable target engagement with weight-based and flat dosing for the respective schedules. The objective of this study was to determine if overall survival (OS) differs ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…One study assessed the safety of this dosing interval in advanced non-small cell lung cancer, and indeed found that there was an increased incidence of toxicity with the 400 mg cohort [ 9 ]. However, alternative studies have found no difference in time to treatment discontinuation nor any difference in overall survival [ 10 , 11 ]. Therefore, based on the findings of our study and current literature, it is reasonable to discern that pembrolizumab 400 mg every 6 weeks is an administration schedule that can be considered not only pharmacokinetically effective, but also safe.…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed the safety of this dosing interval in advanced non-small cell lung cancer, and indeed found that there was an increased incidence of toxicity with the 400 mg cohort [ 9 ]. However, alternative studies have found no difference in time to treatment discontinuation nor any difference in overall survival [ 10 , 11 ]. Therefore, based on the findings of our study and current literature, it is reasonable to discern that pembrolizumab 400 mg every 6 weeks is an administration schedule that can be considered not only pharmacokinetically effective, but also safe.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS for Q6W dosing was 17.1 months compared to 15.1 months for Q3W dosing, with an HR 0.83 (95% CI 0.49-1.42, P = .50). 11 However, there were only 41 patients in the Q6W cohort and the safety profile of these 2 regimens was not assessed. A study of 45 patients with advanced NSCLC, in whom the pembrolizumab dosage was switched from 200 mg Q3W to 400 mg Q6W, raised concern about new or worsening immune-related AEs, especially pneumonitis in 11 (24%) patients.…”
Section: Introductionmentioning
confidence: 99%